The short-run persistence of performance in funds of hedge funds - Ardia, David; Boudt, Kris (New-York: G. N. Gregoriou, 2013)
There is extensive empirical evidence that funds of hedge funds (FoHFs) quickly change their investment bets as a function of the changing market conditions. In this chapter, we first analyze the stability of risk exposure and performance of FoHFs during the period January 2005–June 2011. We then study the short-run persistence of performance in the FoHFs industry. Past performance is measured using the 1-year trailing return as well as risk-adjusted measures such as the Sharpe ratio and the fund’s alpha based on the Carhart (1997) or Fung and Hsieh (2004) factor models. Over the examined timeframe, we consistently find that using risk-adjusted return measures improves the risk-adjusted performance of the momentum investment strategy. This finding holds for the financial crisis period as well as the pre- and post-crisis periods.
Keywords: Alpha; Funds of Hedge funds; Hot hands; Performance; Sharpe ratio